2021
DOI: 10.3389/fpls.2021.777975
|View full text |Cite
|
Sign up to set email alerts
|

A Ratiometric Calcium Reporter CGf Reveals Calcium Dynamics Both in the Single Cell and Whole Plant Levels Under Heat Stress

Abstract: Land plants evolved to quickly sense and adapt to temperature changes, such as hot days and cold nights. Given that calcium (Ca2+) signaling networks are implicated in most abiotic stress responses, heat-triggered changes in cytosolic Ca2+ were investigated in Arabidopsis leaves and pollen. Plants were engineered with a reporter called CGf, a ratiometric, genetically encoded Ca2+ reporter with an mCherry reference domain fused to an intensiometric Ca2+ reporter GCaMP6f. Relative changes in [Ca2+]cyt were estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The Ca 2+ sensor was designed as the mCherry fused to the N-terminus of GCaMP6f and consisted of two tandem fluorescent proteins ( Weigand et al., 2021 ). The protein-based Ca 2+ sensor (GCaMP6fmC) was used as an alternative tool to compare two separate cytoplasmic Ca 2+ influxes in the wild type and Ca 2+ sensor transgenic rice lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ca 2+ sensor was designed as the mCherry fused to the N-terminus of GCaMP6f and consisted of two tandem fluorescent proteins ( Weigand et al., 2021 ). The protein-based Ca 2+ sensor (GCaMP6fmC) was used as an alternative tool to compare two separate cytoplasmic Ca 2+ influxes in the wild type and Ca 2+ sensor transgenic rice lines.…”
Section: Resultsmentioning
confidence: 99%
“…GCaMP6f was cloned into the plant expression vector pGWB554 using standard molecular techniques, as described previously ( Choi et al., 2014 ; Weigand et al., 2021 ). The resultant construct was transformed into rice cultivar Kitaake using Agrobacterium tumefaciens strain LBA4404.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that membranelocalized calcium ion (Ca 2+ ) channels are heat sensors in terrestrial plants [36][37][38]68]. Indeed, many lines of evidence indicate the contribution of Ca 2+ influxes in the early phase of the heat stress response in terrestrial plants [36][37][38][68][69][70]; in moss, the activation of plasma membrane-embedded cyclic nucleotide-gated Ca 2+ channels depends on membrane fluidization [36][37][38]68]. Thus, it is plausible that Ca 2+ channels might be heat sensors that become activated by the heat-induced membrane fluidization in N. yezoensis; however, little is currently known about the heat sensor and heat stress signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In other plants, such as Arabidopsis ( Arabidopsis thaliana ), support for the role of high temperatures in inducing [Ca 2+ ] cyt elevations is mixed, although Ca 2+ elevations are observed within the chloroplast ( Lenzoni and Knight, 2019 ). However, a recent study demonstrated that elevated temperature-induced [Ca 2+ ] cyt elevations in Arabidopsis leaves, but not in pollen tubes ( Weigand et al, 2021 ). Potential temperature sensors in plants include the cold-sensitive regulator of G-protein signaling (COLD1/RGA1) complex in rice ( Oryza sativa ), which is proposed to either function as a Ca 2+ channel or to activate other Ca 2+ channels ( Ma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%